2018
DOI: 10.1139/cjm-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bamboo vinegar powder as an antibiotic alternative on the digesta bacteria communities of finishing pigs

Abstract: This study investigated the use for bamboo vinegar powder as an antibiotic alternative in the diet of growing-finishing pigs by examining their digestive bacterial communities. Forty-five Duroc × Landrace × Yorkshire growing-finishing pigs were randomly allocated to five diet groups: 0%, 0.5%, 1.0%, or 1.5% bamboo vinegar levels and antibiotics. After 37 days, the digesta in duodenum of four pigs from each treatment were analyzed for their bacterial community compositions using 16S rRNA gene sequencing. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Reports found that feeding bamboo vinegar power increased GSH-PX and T-SOD activity. Moreover, BV in the diets of weaned pigs increased the activity of GSH-PX (Chu et al, 2013;Qu et al, 2018). In our study, the GSH-Px activity in serum was higher in laying hens fed BV at 30 days, which indicated that BV could effectively improve the antioxidant status of laying hens and eggs, which may contribute to the increase of albumin contents.…”
Section: Discussionsupporting
confidence: 54%
“…Reports found that feeding bamboo vinegar power increased GSH-PX and T-SOD activity. Moreover, BV in the diets of weaned pigs increased the activity of GSH-PX (Chu et al, 2013;Qu et al, 2018). In our study, the GSH-Px activity in serum was higher in laying hens fed BV at 30 days, which indicated that BV could effectively improve the antioxidant status of laying hens and eggs, which may contribute to the increase of albumin contents.…”
Section: Discussionsupporting
confidence: 54%
“…Controlling pathogens from the source, improving the health supervision system and biosafety route, and selecting some mature antibiotic substitutes (such as Chinese herbal medicine preparations, enzyme preparations, microbial preparations, etc.) can improve the economic benefits of agriculture [ 97 , 98 , 99 ].…”
Section: Countermeasures Of the Chinese Breeding Industry In The Era Of Banning Antibioticsmentioning
confidence: 99%
“…Addition of 1.5% bamboo vinegar powder promotes the growth and development of growing-finishing pigs, increases the abundance of Firmicute / Bacteroidetes , enhances the ability of the host to absorb food energy and store more body fat in 37-days experiments. Additionally, bamboo vinegar powder has positive effects on promoting the abundance of Lactobacillus and Thalassospira and on inhibiting Streptococcus and Prevotella growth ( 98 ). 1% Wakame seaweed powder maybe alter intestinal microflora preferentially, namely, which are observed that an increase in Lactobacillus and a decrease of Escherichia coli to improve the gut health and immunity of pigs ( 99 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%